Assessing Safety Culture Maturity in Indonesia's Petrochemical Producer - Astuti, Putu Nadi; Djunaidi, Zulkifli; Alfiyyah, Arifah (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Safety culture maturity is essential in high-risk industries, including the petrochemical sector, where maintaining workplace safety helps prevent accidents and improve operational efficiency. This study explores the maturity level of safety culture at the petrochemical company in Indonesia using Hudson’s five stage maturity model as a framework for evaluation. The research aims to identify the correlation between safety culture maturity and five aspects of organizational factors. Methods: The questionnaire was completed using online survey-based research by the employees in a petrochemical company of 86 respondents selected through purposive sampling. Safety culture maturity served as the dependent variable, while the independent variables included five organizational factors: information, organizational learning, employee participation, communication, and commitment. The study considers safety culture maturity as the dependent variable, while the five organizational factors serve as independent variables. Data were analyzed using regression analysis Spearman’s correlation to assess between these factors and the maturity level of safety culture. Results: The results from the framework demonstrating the safety culture maturity at the level of generative. The strongest correlations were found in commitment (r = 0.712, p < 0.01), followed by information, organizational learning, employee participation, and communication. Meanwhile, gender and education level did not significantly influence safety culture maturity. Conclusion: These findings highlight the importance of organizational commitment, effective communication, and continuous learning make the safety culture become the habit. The study recommended the petrochemical industries using the framework and revised the questionnaire align with the regulation for continuous improvement in safety culture.